HUBUNGAN ANTARA GAYA BELAJAR DAN RASA PERCAYA DIRI TERHADAP HASIL BELAJAR - A. Nurkidam (Al-Ishlah: Jurnal Pendidikan Islam, 2016)
The learning achievement is influenced by several factors, among others: the style of learning and self-confidence which is owned by a learner. Achievement of learning out comes or quality learning can be demonstrated by learners through the value obtained from any field of study learned. It is recognized that every learner has an assortment of characters and learning styles of its own besides that learners each have a level of confidence that is different. Of course in this case will have an impact on learning out comes of each field of studylearned.